Trifluoromethylated Lithium Borates as Electrolyte Salts for High‐Energy‐Density Lithium‐Ion Batteries with High‐Voltage LiNi0.5Mn1.5O4 Positive Electrodes - Mikihiro Takahashi; Katsumasa Mori; Prof. Dr. Yu Katayama; Prof. Dr. Hiromori Tsutsumi (ChemElectroChem, 2024)
Abstract LiNi0.5Mn1.5O4 (LNMO) is a promising positive electrode material for high‐energy‐density lithium‐ion batteries (LIBs) because of its high working voltage; however, its practical application is hindered by the insufficient oxidation resistance of LIB electrolytes. In this study, we aimed to address this issue by evaluating two trifluoromethylated lithium borate compounds lithium difluoro (perfluoropinacolato) borate (PFP‐F2) and lithium difluoro(2‐hydroxy‐3,3,3,3′,3′,3′‐hexafluoroisobutylato) borate (HHIB‐F2) as electrolyte salts for high‐potential LIBs (4.8 V vs. Li/Li+) with LNMO positive electrodes. In full‐cell tests, the cyclability of LIBs containing these salts is superior (60 °C) to that of the cell with lithium tetrafluoroborate (LiBF4) as the reference electrolyte salt, which is ascribed to the formation of a positive electrode passivation layer that inhibits the oxidative decomposition of the electrolyte salt and solvent in the former case. Moreover, the oxidative decomposition of trifluoromethylated borates at 4.8 V affords a passivation layer on the negative electrode. Thus, the examined borates hold great promise for the commercialization of high‐energy‐density LNMO‐based LIBs, and the formation of a solid electrolyte interphase (SEI) at the negative electrode resulting from the oxidative decomposition products of electrolyte salts is a promising new way to enhance the performance of high‐potential positive electrode LIBs beyond existing levels.